Vascular Change and Opposing Effects of the Angiotensin Type 2 Receptor in a Mouse Model of Vascular Cognitive Impairment. Issue 3 (March 2015) - Füchtemeier, Martina; Brinckmann, Marie P; Foddis, Marco; Kunz, Alexander; Po, Chrystelle; Curato, Caterina; Dirnagl, Ulrich; Farr, Tracy D
Our aims were to assess the spatiotemporal development of brain pathology in a mouse model of chronic hypoperfusion using magnetic resonance imaging (MRI), and to test whether the renin-angiotensin system (RAS) can offer therapeutic benefit. For the first time, different patterns of cerebral blood flow alterations were observed in hypoperfused mice that ranged from an immediate and dramatic to a delayed decrease in cerebral perfusion. Diffusion tensor imaging revealed increases in several quantitative parameters in different brain regions that are indicative of white-matter degeneration; this began around 3 weeks after induction of hypoperfusion. While this model may be more variable than previously reported, neuroimaging tools represent a promising way to identify surrogate markers of pathology. Vascular remodelling was observed in hypoperfused mice, particularly in the anterior part of the Circle of Willis. While the angiotensin II receptor type 2 agonist, Compound 21 (C21), did not influence this response, it did promote expansion of the basilar artery in microcoil animals. Furthermore, C21-treated animals exhibited increased brain lymphocyte infiltration, and importantly, C21 had opposing effects on spatial reference memory in hypoperfused and sham mice. These results suggest that the RAS may have a role in vascular cognitive impairment.